2021
DOI: 10.1177/08912424211000127
|View full text |Cite
|
Sign up to set email alerts
|

Ready for a Close-Up: The Effect of Tax Incentives on Film Production in California

Abstract: Do motion picture incentives nudge productions to film in an adopting state, increase budgets, or hire more cast and filmmakers? Or do they simply subsidize productions that would have occurred regardless? Using California’s Film and Television Tax Credit Program, the author exploits incentives given out by lottery to answer these questions. The author finds that 19% of films would have filmed in California even without a tax incentive, but that the offering of an incentive increased the probability of a film … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…There are a few evaluations of California's film credits, only one of which provides evidence that might reflect a positive causal effect of the credits. Workman (2021) studied an earlier version (Film & Television Tax Credit Program 1.0) that had a randomization feature allowing rigorous evidence. Workman found that the offer of a tax credit increased the number of cast members and filmmakers in California by an average of 123%, and those firms that received a tax credit increased the number of cast members and filmmakers in California by an average of 388%.…”
Section: Tax Creditsmentioning
confidence: 99%
“…There are a few evaluations of California's film credits, only one of which provides evidence that might reflect a positive causal effect of the credits. Workman (2021) studied an earlier version (Film & Television Tax Credit Program 1.0) that had a randomization feature allowing rigorous evidence. Workman found that the offer of a tax credit increased the number of cast members and filmmakers in California by an average of 123%, and those firms that received a tax credit increased the number of cast members and filmmakers in California by an average of 388%.…”
Section: Tax Creditsmentioning
confidence: 99%
“…However, in the face of the modernist trend and the general environment of contemporary art, Chinese video art started a little later, but its development was more rapid, from the initial video art, only after this year, it had already shifted to video technology [10]. In other words, the works created by different video artists [11] not only carry their diverse forms of thought, but also their personal characteristics. The emergence of this phenomenon, however, also means that there is a wide variation in the results of video art in mainland China.…”
Section: An Analysis Of the Development Of Video Art In Mainland Chinamentioning
confidence: 99%